Utilization of Waste Crab and Wood Skin As Biodegradable - Sariwahyuni Sariwahyuni; Herlina Rahim; Misbahuddin (YCMM, 2022)
Biodegradable plastics are an important thing to consider in order to meet environmentally friendly plastics. This study aims to determine the potential of crab waste and cassava peel waste as raw material for biodegradable plastics. This research was conducted in the Laboratory of Microbiology Industry at the Technical Industry Academy of Makassar in Januari-April 2022. The research method used was an experimental method with simple statistical analysis techniques. This research uses three parameters : the power of elasticity, resistance to temperature and the ability to decompose. The result that chitosan concentration of 1 gram, 5 grams of starch and cassava peel, 15 ml glycerol gave the best results compared to the two other treatments at 4,623% elongation values​​, degraded faster and has a resistance to temperatures up to 100 ℃ for 2 hours